Greenwashing in Sustainability Reports: Analysis of ESG Disclosure Quality in Multinational and Indonesian Companies - Luffi Lestari; Massagar Al Sya’ban; Marliani Marliani; Yusnaini Yusnaini (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This research is focused on assessing the caliber of Environmental, Social, and Governance (ESG) disclosures within sustainability reports, while also examining patterns of greenwashing activities in multinational corporations and firms in Indonesia. The research utilized the Systematic Literature Review (SLR) approach, analyzing 31 articles indexed in Scopus and SINTA from 2020 to 2026. The review's findings indicate that a higher level of ESG disclosures does not necessarily signify a real enhancement in the execution of sustainable practices. Various studies point out discrepancies between details presented in the reports and the actual performance related to ESG, suggesting the likelihood of greenwashing. In comparison, multinational corporations generally produce more organized reports and align with international guidelines, although there remains a tendency for selective reporting. Conversely, Indonesian companies are making progress in sustainability reporting; however, the uniformity and thoroughness of disclosures across ESG areas, particularly environmental matters, still show inconsistencies. This research highlights that the quality of disclosures regarding thoroughness, fairness, consistency, and trustworthiness of information is more crucial than simply counting the indicators mentioned. These results add to knowledge concerning ESG and greenwashing and provide insights for regulators and stakeholders to enhance the clarity and reliability of sustainability reports.